2005
DOI: 10.1080/1043859042000304043
|View full text |Cite
|
Sign up to set email alerts
|

Does the digital divide matter? The role of information and communication technology in cross-country level and growth estimates

Abstract: two anonymous referees for useful comments and suggestions. The usual disclaimer applies.2 Does the digital divide matter ? The ICT role in cross-country level and growth estimates AbstractThe bulk of Information and Communication Technology is made of weightless, implementable and infinitely reproducible knowledge products (such as software and databases). These products are transferred by telephone lines, accessed through internet hosts and processed and exchanged through personal computers. In this work, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…However, Becchetti and Adriani (2005), in an ICT augmented version of the Mankiw et al (1992) model, found that ICT components, such as telephone lines, personal computers, mobile phones, and internet hosts, significantly affect levels and growth of income per worker, across a sample of developed and developing countries in the period 1985-1997. Similar evidence is provided by Kraemer and Dedrick (2001), in a study including 12 Asian and Pacific countries, where a significant ICT effect on output and productivity is established.…”
Section: Related Researchmentioning
confidence: 98%
See 2 more Smart Citations
“…However, Becchetti and Adriani (2005), in an ICT augmented version of the Mankiw et al (1992) model, found that ICT components, such as telephone lines, personal computers, mobile phones, and internet hosts, significantly affect levels and growth of income per worker, across a sample of developed and developing countries in the period 1985-1997. Similar evidence is provided by Kraemer and Dedrick (2001), in a study including 12 Asian and Pacific countries, where a significant ICT effect on output and productivity is established.…”
Section: Related Researchmentioning
confidence: 98%
“…This early research, which was based mainly on firm and industry level data, showed that there was no statistically significant, or even measurable, relationship between ICT and productivity at any level of analysis. However, Becchetti and Adriani (2005) note that more recently, as new data were made available and new methodologies were applied, empirical investigations have found evidence that, in the second part of the 1990s, ICT investment was associated with improvements in productivity and economic growth (Brynjolfsson, and Hitt, 1996;Siegel, 1997;Lehr and Lichtenberg, 1999;Brynjolfsson and Hitt, 2000;Oliner and Sichel, 2000;Jorgenson and Stiroh, 2000). Similar evidence is found even after 2000, despite the 2001 recession and the downward revision of the US GDP (gress domestic product) and the recession beginning in March 2001 (Jorgenson et al, 2002;Oliner and Sichel, 2002).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies by Jorgenson, Ho, and Stiroh (2002), Colecchia and Schreyer (2002), Van Ark et al (2002), Schreyer (2000), Daveri (2002), andOECD (2003) are at the cross-country aggregate level. At the aggregate level are studies by Dewan and Kraemer (2000) and Becchetti and Adriani (2005), which cover a large number of both developed and developing countries. From these studies, it seems safe to conclude that the impact of ICT on economic growth and labor productivity has been positive and mostly statistically significant in developed economies.…”
Section: Ict and Economic Growth In Developed Countriesmentioning
confidence: 99%
“…Today's wage premiums are estimated to range between 8% and 25%, varying in accordance to the way computers are used (e.g., Lee & Jonghyuk, 2004;Tashiro, 2004). Cross-country evidence emphasizes the positive effects of new technologies on levels and growth of income per worker (Becchetti & Adriani, 2005). Although the effect of Internet use on income seems to be decreasing, the wage premium for computer use remains more or less stable (Lee & Jonghyuk, 2004).…”
mentioning
confidence: 98%